Bare laser-synthesized palladium–gold alloy nanoparticles as efficient electrocatalysts for glucose oxidation for energy conversion applications. Issue 23 (14th October 2020) - Holade, Yaovi; Hebié, Seydou; Maximova, Ksenia; Sentis, Marc; Delaporte, Philippe; Kokoh, Kouakou Boniface; Napporn, Teko W.; Kabashin, Andrei V.
Abstract : Laser-synthesized PdAu nanoparticles demonstrate a strong synergetic effect on glucose oxidation combining high catalytic activity with ultrafast kinetics at low potentials. Abstract : Electrochemical energy converters based on biomass-based organic molecules such as glucose have recently demonstrated great potential for the development of functional bioimplantable devices such as pacemakers, but such converters lack efficient metal-based anode nanocatalysts, which could combine the stability of parameters with high performance. Here, we elaborate a technique of femtosecond laser ablation in water to synthesize bare (ligand-free) PdAu alloy nanoparticles with constituents having a variable ratio and explore these nanoparticles as electrocatalysts for glucose oxidation. Our data evidence that the combination of two metals in one bare nanoformulation can result in a strong synergetic effect, which makes the combination of high catalytic activity toward glucose oxidation with ultrafast kinetics at low potentials possible due to the presence of Au and Pd, respectively, while a bare uncontaminated surface ensures outstanding catalytic performance. We show that at an optimal ratio of constituents (50%/50%), PdAu nanoparticles can provide a mass activity of 60 A g −1 and an onset potential lower than 0.27 V vs. RHE, which outperform all currently existing nanoparticle-based electrodes. Our results show that bare nanomaterials prepared by laser-ablation synthesis can offer much improved characteristics as electrocatalysts for energy conversion and storage applications, while the versatility of laser synthesis can be extended to other alloy architectures in order to provide optimal characteristics for a concrete catalytic process.